Short Duplex Module Coupled to G-Quadruplexes Increases Fluorescence of Synthetic GFP Chromophore Analogues - Snizhana O. Zaitseva; Nadezhda S. Baleeva; Timofei S. Zatsepin; Ivan N. Myasnyanko; Anton V. Turaev; Galina E. Pozmogova; Alexei A. Khrulev; Anna M. Varizhuk; Mikhail S. Baranov; Andrey V. Aralov (Sensors, 2020)
Aptasensors became popular instruments in bioanalytical chemistry and molecular biology. To increase specificity, perspective signaling elements in aptasensors can be separated into a G-quadruplex (G4) part and a free fluorescent dye that lights up upon binding to the G4 part. However, current systems are limited by relatively low enhancement of fluorescence upon dye binding. Here, we added duplex modules to G4 structures, which supposedly cause the formation of a dye-binding cavity between two modules. Screening of multiple synthetic GFP chromophore analogues and variation of the duplex module resulted in the selection of dyes that light up after complex formation with two-module structures and their RNA analogues by up to 20 times compared to parent G4s. We demonstrated that the short duplex part in TBA25 is preferable for fluorescence light up in comparison to parent TBA15 molecule as well as TBA31 and TBA63 stabilized by longer duplexes. Duplex part of TBA25 may be partially unfolded and has reduced rigidity, which might facilitate optimal dye positioning in the joint between G4 and the duplex. We demonstrated dye enhancement after binding to modified TBA, LTR-III, and Tel23a G4 structures and propose that such architecture of short duplex-G4 signaling elements will enforce the development of improved aptasensors.